ROLE OF MAHATMA GANDHI IN THE PURSUIT OF VALUES BASED HUMAN SATYAGRAHA - Lestiana '; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Human values always coveted by all mankind in creating an Organized structure, dynamic and progressive. An order-which emphasizes Basically the message of peace, justice, order, freedom, and other humanitarian messages. HOWEVER, there is some interest for certainement parties That Are mastered and controlled as the invaders That Certain menguasaidaerah. Through policies notes many of the rights of the people who colonized ignored. The policy would Violate the very nature of human values zoals the right to mengeluakan opinion, the right to vote, the right to life and the basic human rights of others. The purpose of this study was to determining the biography of Mahatma Gandhi, to know what efforts were made by Mahatma Gandhi in the fight for human values based on the principles of Satyagraha, To know the obstacles faced by Mahatma Gandhi in the fight for human values , to knowing the end of the struggle of Mahatma Gandhi. This research method is historical. The historical method is a way to revive the event or Events that occurred in the past. The goal is to reconstruct the Past Systematically and Objectively, by collecting, Evaluating, verifying and systematize the evidence to get the facts and Obtain the Conclusions That can be dipertangungg Justified. The results Showed That Mahatma Gandhi is known as a leader who led the people of India to escape from the shackles of British rule with berasaskan peace. As a follower of Hinduism, Gandhi apply Their religion to inspire the world in order to renounce violence, Uphold human rights, and freedom. He is fighting for the rights of the Indian people in South Africa and in India withoutusing elements of violence. Gandhi apply the doctrine of Ahimsa (reject the desire to kill and endanger the life or love peace), Swadeshi (use products made in their Own Country), and ocher (mass strike in Rejecting the British government regulations) in-which all of the teaching AIMS to Obtain the truth (Satyagraha).Keyword : Role, Mahatma Gandhi, values Humanity